Mechanically strong MXene/Kevlar nanofiber composite membranes as high-performance nanofluidic osmotic power generators - Zhang, Zhen; Yang, Sheng; Zhang, Panpan; Zhang, Jian; Chen, Guangbo; Feng, Xinliang (Nature communications, 2019)
Two-dimensional nanofluidic channels are emerging candidates for capturing osmotic energy from salinity gradients. However, present two-dimensional nanofluidic architectures are generally constructed by simple stacking of pristine nanosheets with insufficient charge densities, and exhibit low-efficiency transport dynamics, consequently resulting in undesirable power densities (<1 W m −2 ). Here we demonstrate MXene/Kevlar nanofiber composite membranes as high-performance nanofluidic osmotic power generators. By mixing river water and sea water, the power density can achieve a value of approximately 4.1 W m −2 , outperforming the state-of-art membranes to the best of our knowledge. Experiments and theoretical calculations reveal that the correlation between surface charge of MXene and space charge brought by nanofibers plays a key role in modulating ion diffusion and can synergistically contribute to such a considerable energy conversion performance. This work highlights the promise in the coupling of surface charge and space charge in nanoconfinement for energy conversion driven by chemical potential gradients. Nanofluidic channels can capture osmotic energy from salinity gradients, but output power densities should be improved for practical applications. Here the authors report high-strength nanosheet/nanofiber composite membranes for harvesting osmotic energy from natural water with high output power.